Immunomodulation in Middle‐Aged Humans Via the Ingestion of Physta® Standardized Root Water Extract of Eurycoma longifolia Jack—A Randomized, Double‐Blind, Placebo‐Controlled, Parallel Study. (27th January 2016) - George, Annie; Suzuki, Naoko; Abas, Azreena Binti; Mohri, Kiminori; Utsuyama, Masanori; Hirokawa, Katsuiku; Takara, Tsuyoshi
Abstract : This study was aimed to investigate the capacity of a standardized root water extract of Eurycoma longifolia (Tongkat Ali, TA), Physta® to modulate human immunity in a middle‐aged Japanese population. This randomized, double‐blind, placebo‐controlled, parallel study was conducted for 4 weeks. Eighty‐four of 126 subjects had relatively lower scores according to Scoring of Immunological Vigor (SIV) screening. Subjects were instructed to ingest either 200 mg/day of TA or rice powder as a placebo for 4 weeks [TA and Placebo (P) groups] and to visit a clinic in Tokyo twice (weeks 0 and 4). SIV, immunological grade, immunological age, and other immune parameters were measured. Eighty‐three subjects completed the study; 40 in the TA group and 41 in the P group were statistically analyzed, whereas two were excluded from the analyses. At week 4, the SIV and immunological grade were significantly higher in the TA group than those in P group ( p < 0.05). The numbers of total, naïve, and CD4 + T cells were also higher in the TA group than those in P group ( p < 0.05). No severe adverse events were observed. The results suggest that ingestion of the root water extract of TA (Physta®) enhances comprehensive immunity in both middle‐aged men and women. This study is registered in UMIN‐CTR (UMIN000011753). Copyright © 2016 John Wiley & Sons, Ltd.